2019
DOI: 10.3892/mmr.2019.10202
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the P2X7 receptor in temporal lobe epilepsy: Animal models and clinical evidence

Abstract: Previous studies have indicated that the adenosine triphosphate-sensitive homomeric P2X7 receptor (P2X7R) plays an important role and exhibits therapeutic potential in a number of brain disorders, including temporal lobe epilepsy (TLE). The aim of the present study was to assess the expression of P2X7R, glutamate (GLU) and glial fibrillary acidic protein (GFAP) in the temporal neocortex and hippocampus of rats with lithium-pilocarpine-induced epilepsy as well as in patients with intractable TLE. The results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…This is in agreement with the association of P 2X7 R polymorphisms with depressive symptoms (see meta-analysis in Czamara et al, 2018) and reinforces the concept of ATP as a danger signal in brain dysfunction (reviewed in Rodrigues et al, 2015). As observed by others in different animal models of brain dysfunction (Jimenez-Pacheco et al, 2013;Wang et al, 2017;Martínez-Frailes et al, 2019;Song et al, 2019), namely upon chronic stress (Yue et al, 2017;Dang et al, 2018; but see Kongsui et al, 2014), we identified an up-regulation of P 2X7 R and an ability of P 2X7 R to control different markers of neuroinflammation, as also reported in other animal models of depression (Yue et al, 2017;Bhattacharya and Jones, 2018), to mediate stress-induced behavioral modifications (Rial et al, 2016;Deng et al, 2020;Troubat et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…This is in agreement with the association of P 2X7 R polymorphisms with depressive symptoms (see meta-analysis in Czamara et al, 2018) and reinforces the concept of ATP as a danger signal in brain dysfunction (reviewed in Rodrigues et al, 2015). As observed by others in different animal models of brain dysfunction (Jimenez-Pacheco et al, 2013;Wang et al, 2017;Martínez-Frailes et al, 2019;Song et al, 2019), namely upon chronic stress (Yue et al, 2017;Dang et al, 2018; but see Kongsui et al, 2014), we identified an up-regulation of P 2X7 R and an ability of P 2X7 R to control different markers of neuroinflammation, as also reported in other animal models of depression (Yue et al, 2017;Bhattacharya and Jones, 2018), to mediate stress-induced behavioral modifications (Rial et al, 2016;Deng et al, 2020;Troubat et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The original finding, that SE induces an up-regulation of P2X7R-IR in epilepsy-relevant areas of the brain (hippocampus, neocortex), was observed repeatedly both in human and rodent tissues (e.g., [ 87 , 88 , 89 ]. In consequence, it was logical to suggest that damage to neurons by pathological, high frequency firing during epileptic fits may cause a massive release of ATP and the consecutive activation of P2X7Rs located in the first line at microglial cells; this is expected to release bioactive, detrimental molecules (see Section 2 ).…”
Section: Epilepsymentioning
confidence: 99%
“…Similarly to AD, P2X7R protein levels are upregulated in regions damaged by seizures and in the hippocampus of animal models. As previously summarized (Engel et al, 2012;Engel et al, 2016), the lack of the P2X7R promotes susceptibility to status epilepticus, while P2X7R antagonists are potent anticonvulsants (Engel et al, 2012;Engel et al, 2016;Beamer et al, 2017;Zeng et al, 2017;Burnstock and Knight, 2018;Song et al, 2019;Doǧan et al, 2020;Hong et al, 2020;Morgan et al, 2020). P2Y2R knockout animals present higher glutamate release in the hippocampus (Alhowail et al, 2020), and uridine triphosphate administration had sleep-promoting and anti-epileptic actions, improved memory function and affected neuronal plasticity (Dobolyi et al, 2011;Alves et al, 2017).…”
Section: Epilepsymentioning
confidence: 89%